Commented translation of Erwin Schrödinger's paper 'On the dynamics of elastically coupled point systems' (Zur Dynamik elastisch gekoppelter Punktsysteme). (January 2021) - Mühlich, Uwe; Abali, Bilen Emek; dell'Isola, Francesco
The paper ' Zur Dynamik elastisch gekoppelter Punktsysteme ' by Schrödinger (1914) does not seem to have attracted the attention that it deserves. We translate it into English here and we discuss its results in detail, with a view to its possible influence in the modern theories of generalised continua. The clever solution found, in terms of Bessel functions, by Schrödinger of the problem of the vibrations of a linear infinite chain of molecules gives some important methodological hints for contemporary research.